Development, RSM-based modeling, and process optimization of an ultrasonic coating system for extending the storage life of fresh fruits - Mohammed, Maged; Alqahtani, Nashi K.; Ali, Salim A. (Frontiers in Sustainable Food Systems, 2024)
Effective and innovative freshly produced preservation methods are paramount for ensuring safe and sustainable food. Edible coatings for fresh dates can provide an additional protective layer to enhance their shelf life and extend marketability. However, the optimum coating requires a high uniformity of coating layer on the fruit. The ultrasonic coating can achieve a more uniform and consistent coating on the fruit surface. Therefore, this study aimed to design, evaluate, and optimize the process parameters of an innovative ultrasonic coating system (UCS) to enhance the shelf life and quality of fresh date palm fruit utilizing gum Arabic as an edible coating. The response surface methodology (RSM) was conducted using Design-Expert software Version 13. The central composite design was employed to determine the influence of eight independent variables, namely, coating time, air flow rate, liquid height above the ultrasonic transducers, liquid temperature, edible gum Arabic concentration, drying time for coated fruit, drying temperature, and storage temperature on the responses which were fruit shelf life, ripe fruit percentage, color changes, and weight loss. The optimization was conducted to determine the optimal solutions for enhancing fruit shelf life and quality. The optimal optimization outcome with the desirability of 0.90 demonstrated that coating fresh date palm fruits with a gum Arabic concentration of 9.58% at an air flow rate of 1.95 m/s, a height of liquid above the ultrasonic transducer of 0.62 cm, a liquid temperature of 40°C, a drying time of 7.4 min, a drying temperature of 30°C, and a storage temperature of 5°C resulted in extending the shelf life of the stored fruits to 65 days with 3.47 ripening percentage, 7.39 color change, and 4.22% fruit weight loss. The validation experiment conducted at the same independent variable levels indicated that the fruit shelf life extended to 60.2 ± 0.5 days, accompanied by a ripening percentage of 3.4 ± 0.4%, a color change of 10.3 ± 0.9, and a fruit weight loss of 5.4 ± 0.9%. The solutions were validated through rigorous experiments on fresh date palm fruit at the Khalal stage. The findings showed a positive response for fruit shelf life with a slight decrease in the percentage of fruit ripe, color change, and weight loss.